Studies on antibiotic compounds of methanol extract of Curculigo latifolia dryand - Lim Sheh Hong; Darah Ibrahim (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
A research was conducted to study the effect of different parts of the extracts from Curculigo latifolia Dryand plant.  They were from the roots, stems and leaves by using methanol as the extraction solvent.  The antimicrobial activity of methanol extract from Curculigo latifolia Dryand was then performed on various tested bacteria, yeasts and fungi.  The results revealed that the extracts possessed antimicrobial activities on all of tested bacteria and yeasts. However, all the tested fungi exhibited resistant against all the different parts of Curculigo latifolia Dryand extracts. The minimum inhibitory concentration (MIC) and minimum lethality concentration (MLC) of the Curculigo latifolia Dryand extracts against bacteria and yeast cells were determined and the mode of action of the roots extract on the cells was studied by means of microscopy